STRATEGI MASJID SABILILLAH MALANG DALAM PEMBERDAYAAN EKONOMI UMAT - Aki Edi Susanto (UIN Mataram, 2020)
“The Strategy of the Malang Sabilillah Mosque in Community Economic Empowerment”. With the aim of this study is to understand and explore how the mosque’s strategy in the economic empowerment of the people and to understand how the results of the mosque’s strategy in the economic empowerment of the people. The research method used is to use a case study approach and descriptive qualitative research type. Data collection techniques using interviews, observation, documentation and study of literature, which is related to the strategy of the Sabilillah Mosque in Malang in empowering the economic community. The results showed that the community economic empowerment strategy used by the Sabilillah Mosque in Malang was to use two different empowerment programs, but the two programs were interrelated wih each other. Mosque cooperatives explore the potential of pilgrims who want to open a businesses, while LAZIS has a business development programs for the poor or needy to empower them from the economic side. Then the results of the empowerment strategy stated that the micro entrepreneurs who were given assistance from the mosque made their businesses grow and affect the economic welfare of the family.